Synergy of Humanistic Pedagogy and a Flexible Curriculum in Supporting Mental Well-Being and Academic Achievement - Muhamad Hanif Fuadi; Muhammad Yani (Khazanah: Journal of Islamic Education and Science, 2026)
This study was motivated by the increasing complexity of contemporary educational challenges, which extend beyond academic achievement to include students’ mental well-being. Conventional education systems that tend to be rigid and cognitively oriented were considered insufficient to address holistic learning needs. Therefore, this study aimed to analyze the synergy between humanistic pedagogy and a flexible curriculum in supporting mental well-being and academic achievement. This study employed a descriptive qualitative approach with a meta-analysis method of scientific literature published between 2018 and 2025 from reputable databases. Data collection was conducted through systematic digital documentation procedures, while data analysis used thematic analysis to identify patterns and relationships among variables. The findings indicated that the integration of humanistic pedagogy and a flexible curriculum significantly contributed to improving mental well-being, which subsequently functioned as a mediating variable in enhancing academic achievement. This study provided theoretical contributions in the form of an integrative conceptual model and practical contributions as a basis for strengthening educational policies and learning practices that are more adaptive and responsive to students’ needs.